Creativity and psychopathology: an interdisciplinary view - Holm-Hadulla, Rainer M.; Hofmann, Frank-Hagen; Sperth, Michael; Mayer, Claude-Hélène (Psychopathology, 2021)
Since ancient philosophy, extraordinary creativity is associated with mental disorders, emotional and cognitive destabilization, and melancholia. We here summarize the results of empirical and narrative studies and analyze the most prominent case of a highly creative person who suffered from dysthymia and major depression with suicidality. Hereby, we focus on the interaction of different phases of the creative process with “bipolar” personality traits. Finally, we offer an interdisciplinary interpretation of the creative dialectics between order and chaos. The results show that severe psychopathology inhibits creativity. Mild and moderate disorders can inspire and motivate creative work but are only leading to new and useful solutions when creators succeed in transforming their emotional instability and cognitive incoherence into stable and coherent forms. The cultural idea that creativity emerges in dialectical processes between order and chaos, is also to be found in the psychologic interplay of coherence and incoherence, and in neuro-scientific models of the dynamics between tightening and loosening of neuronal structures. Consequences are drawn for the psychotherapeutic treatment of persons striving for creativity.
Online veröffentlicht: 16. Dezember 2020
Gesehen am 29.01.2024